The First Observation of the Formation of Persistent Aminoxyl Radicals and Reactive Nitrogen Species on Photoirradiated Nitrogen-Containing Microplastics - Zhu, Kecheng; Jia, Hanzhong; Jiang, Wenjun; Sun, Yajiao; Zhang, Chi; Liu, Ze; Wang, Tiecheng; Guo, Xuetao; Zhu, Lingyan (Environmental science & technology, 2022)
Nitrogen-containing microplastics (N-MPs) are widely present in the atmosphere, but their potential health risks have been overlooked. In this study, the formation of persistent aminoxyl radicals (PAORs) and reactive nitrogen species (RNSs) on the N-MPs under light irradiation was investigated. After photoaging, an anisotropic triplet with the g-factor of ∼2.0044, corresponding to PAORs, was detected on the nonaromatic polyamide (PA) rather than amino resin (AmR) by electron paramagnetic resonance and confirmed by density functional theory calculations. The generated amine oxide portions on the photoaged PA were identified using X-ray photoelectron spectroscopy and Raman spectroscopy, which were considered to be the main structural basis/precursors of a PAOR. Surprisingly, RNSs were also observed on the irradiated PA. The generated ·NO due to the aphotolysis of nitrone groups simultaneously reacted with peroxide radicals and O2·– to yield ·NO2 and peroxynitrite, respectively, which were responsible for peroxyacyl nitrates (PAN) and CO3·– formation. Besides, a significantly higher oxidative potential and reductive potential were observed for the aged PA than AmR, which is assigned to the abundant RNSs, organic hydroperoxides and PANs, and a strong ability to transfer electrons from PAOR, respectively. This work provides important information for the potential risks of airborne N-MPs and may serve as a guide for future toxicological assessments.